A friend of Ricardo Palma: Celso Víctor Torres - Ángeles Caballero, César (2016)
Celso Víctor Torres, “Palma ancashino”, was born in Caraz (Villa San Idelfonso, capital of the Province of Huaylas) on July 28, 1860 of the marriage of Eusebio Torres and Antonia Figueroa. The details of his primary and secondary education are of little interest, much less his administrative work; Yes, we refer to the circumstance exercised by the State Notary since 1888, because, perhaps, in the daily trajinar of old and dusty papers and judicial cases he was able to capture the thematic variable of his Traditions. After the daily exercise of a notary, from 1903, the judicial frequency increases with the exercise of the public notary, until his death on November 12, 1918, at nine thirty in the morning in the city of Caraz itself. (Torres Guerrero, 1957, pp. 19-13).